Relação entre o controle glicêmico e a altura final em pacientes com diabetes mellitus tipo 1 - ALMEIDA, Alícia Duarte de (2024)
Background: Type 1 diabetes mellitus is one of the most common chronic diseases in childhood and adolescence. Complications of the disease arise in the short and long term, one of them being the possible impact on height growth. Objectives: To verify the relationship between glycemic levels and the final height of patients with Type 1 Diabetes Mellitus compared to the mean height of the population, according to WHO. Methods: A retrospective, quantitative and descriptive study was carried out with patients with T1DM at the Hospital Universitário João de Barros Barreto, who were followed up at the Ambulatório de Patologias Endócrinas, through the consultation of physical and electronic medical records. Results: 58 patients (29 men and 29 women) participated in the study. The average age at diagnosis was 9,95 years, the average final height was 8,5 cm lower, compared to the population average recommended by the WHO and the Z-Score of final height was negative in both genders with average of -1,28 (土1,15), being -1,08 (土1,15) in females and -1,45 (土1,15) in males. The male gender was further from 0 on the Z-Score curve and had an average of 5 years, for a longer period of illness. Patients, of both sexes, who had final height data and average HbA1C values during the ages of 5 to 19, were allocated into three groups (A, B and C), with values below 9,5% for group A, group B values greater than or equal to 9,5% and less than or equal to 11%, and in group C greater than 11%. It was possible to notice smaller height in group C and when performing the correlation between group A-B (p 0,021), B-C (p NS), C-A (p 0,001), it was possible to report a more significant difference between group C-A, representing the average difference height of 1,75 cm. Using linear regression, it is possible to indicate that, with an increase in each percentage unit of glycated hemoglobin, the average height of the group of patients studied decreases by 0,275 cm. Conclusions: The present study demonstrated that the average final height of patients with T1DM is smaller than the population average recommended by the WHO curve and the Z-score values were negative for both groups. Associated with this, a positive correlation was observed between the levels of glycated hemoglobin and the reduction in final height, inferring that the lack of glycemic control interferes with height growth.